2014
DOI: 10.3389/fnbot.2014.00015
|View full text |Cite
|
Sign up to set email alerts
|

How much time has passed? Ask your heart

Abstract: Internal signals like one's heartbeats are centrally processed via specific pathways and both their neural representations as well as their conscious perception (interoception) provide key information for many cognitive processes. Recent empirical findings propose that neural processes in the insular cortex, which are related to bodily signals, might constitute a neurophysiological mechanism for the encoding of duration. Nevertheless, the exact nature of such a proposed relationship remains unclear. We aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 37 publications
3
36
2
Order By: Relevance
“…Additionally, it is important to note that for our data baseline ANS measures were not systematically related to pre‐TSST time reproductions. This contrasts with prior studies that have found effects of resting state ANS variables on time perception (e.g., Cellini et al, ; Pollatos et al, ).…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Additionally, it is important to note that for our data baseline ANS measures were not systematically related to pre‐TSST time reproductions. This contrasts with prior studies that have found effects of resting state ANS variables on time perception (e.g., Cellini et al, ; Pollatos et al, ).…”
Section: Discussioncontrasting
confidence: 94%
“…The stimuli were presented in E-Prime 2.0 (E-Prime, Pittsburgh, PA) and were displayed for 400, 1,650, 2,900, or 4,150 ms. These durations were chosen to provide four evenly spaced time points spanning a range from fewer than 500 ms to more than 4,000 ms; different subsets of this range have been examined in other studies of time distortion (e.g., Bar-Haim et al, 2010;Mereu & Lleras, 2013;Tipples, 2011), though previous studies tended to focus on either the shorter or longer end of the range and beyond (for exceptions, see Lewis & Miall, 2003;Pollatos, Yeldesbay, Pikovsky, & Rosenblum, 2014). Following the practice, participants completed a prestress measure of time distortion.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, one such study found that individuals with higher resting HRV were more accurate in a DR task (Pollatos et al, 2014). Another study found that individuals were more accurate in this task when they had a higher rate of heart rate slowing during the encoding of intervals (Meissner and Wittmann, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, while our results might suggest that participants intuitively used the rhythm of their own heart as a pacemaker in order to judge the regularity of the stimulus, we do not believe that they provide direct support for any account of the cognitive processes involved in time estimation (Muller and Nobre, 2014;Wittmann, 2009). Our interpretation of our results thus does not regard the heart as an endogenous clock-type system for time estimation (but see Craig, 2009b;Meissner and Wittman, 2011;Pollatos et al, 2014) and such considerations are beyond the scope of this study (for a discussion of this issue see Wittmann, 2009). Instead, what we propose is that the statistical correlation between the visual flashes and the internal heartbeat pulses had an impact in the subjective experience of the perception of the flashing rhythm.…”
Section: Discussionmentioning
confidence: 67%
“…Internal bodily states can drive cognition and behaviour, with or without awareness (Critchley and Harrison, 2013;Garfinkel et al, 2015), and profoundly influence various dimensions of emotional experience, such as pain perception, emotional reactivity and social decision-making (e.g. Pollatos et al, 2012Pollatos et al, , 2014Herbert et al,. 2007;Garfinkel et al, 2014;Gray et al, 2012;Lenggenhager et al, 2013;Dunn et al, 2012;Durlik et al, 2014).…”
Section: Introductionmentioning
confidence: 99%